Zero-valent iron particles for PCB degradation and an evaluation of their effects on bacteria, plants, and soil organisms - Ševců, Alena; El-Temsah, Yehia S; Filip, Jan; Joner, Erik J; Bobčíková, Kateřina; Černík, Miroslav (Environmental science and pollution research international, 2017)
Two types of nano-scale zero-valent iron (nZVI-B prepared by borohydride reduction and nZVI-T produced by thermal reduction of iron oxide nanoparticles in H2) and a micro-scale ZVI (mZVI) were compared for PCB degradation efficiency in water and soil. In addition, the ecotoxicity of nZVI-B and nZVI-T particles in treated water and soil was evaluated on bacteria, plants, earthworms, and ostracods. All types of nZVI and mZVI were highly efficient in degradation of PCBs in water, but had little degradation effect on PCBs in soil. Although nZVI-B had a significant negative impact on the organisms tested, treatment with nZVI-T showed no negative effect, probably due to surface passivation through controlled oxidation of the nanoparticles.
Keywords: Plants; železo; Oligochaeta; polychlorované bifenyly; Nanoparticles; Iron; Ecotoxicity; Zero-valent iron nanoparticles and microparticles; Polychlorinated biphenyls; Soil Pollutants; látky znečišťující půdu; oxidace-redukce; půda; zvířata; Crustacea; Environmental Restoration and Remediation; Ostracods; nanočástice; Oxidation-Reduction; Earthworms; regenerace a remediace životního prostředí; korýši; Bacteria; Animals; Soil; Polychlorinated Biphenyls; Remediation